The Importance of Accurate Budgeting in Achieving Company Financial Goals - Khaddafi, Muammar; Zahra, Siti Aqila; Safitri, Irma; Salsabila, Viya Aurelia; Ramadhan, Chairy (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
This journal aims to explain the background of company management, which is not much different from project management which is intended to provide guarantees for achieving blueprint results regarding long-term programs. The budget preparation process includes preparing budget representations, preparing short-term process plans, as well as orientation to company profits. Selection of plans is based on the impact of planned activities on profits. Therefore, the budget preparation process is often carried out by preparing short-term profit planning plans. Top management involves selecting activity plans that can influence the success and profits of the company. Management uses profit and business volume analysis techniques. Analysis of these benefits provides information that allows management to select various alternative activities to be adjusted in planning. Once an activity plan is selected to achieve company targets, the responsible manager needs to implement the plan. This requires resource allocation to enable it to achieve the set targets. The method used to collect data involves library research, by collecting relevant data from books, dictionaries, journals, papers and other sources without forgetting to review the field. Based on research carried out based on existing literature reviews, the results of the research data will be the basis for formulating company plans and implementing them thoroughly to achieve effective control over various company activities in accordance with predetermined plans.